2015
DOI: 10.1016/j.ajhg.2015.02.017
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic Analyses Reveal Mutational Signatures and Frequently Altered Genes in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is one of the most common cancers worldwide and the fourth most lethal cancer in China. However, although genomic studies have identified some mutations associated with ESCC, we know little of the mutational processes responsible. To identify genome-wide mutational signatures, we performed either whole-genome sequencing (WGS) or whole-exome sequencing (WES) on 104 ESCC individuals and combined our data with those of 88 previously reported samples. An APOBEC-mediated mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
370
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 296 publications
(409 citation statements)
references
References 49 publications
(94 reference statements)
31
370
3
Order By: Relevance
“…Mutations have been observed in the cell-cycle regulatory pathway genes TP53 (88%), CDKN2A (8%), and RB1 (2%) [35] . In addition, ESCC tumors show amplification of CCND1, which encodes for cyclin D1, and deletion of CDKN2A/ B, which encodes for p16 and p14.…”
Section: Cell Cycle Regulationmentioning
confidence: 99%
See 3 more Smart Citations
“…Mutations have been observed in the cell-cycle regulatory pathway genes TP53 (88%), CDKN2A (8%), and RB1 (2%) [35] . In addition, ESCC tumors show amplification of CCND1, which encodes for cyclin D1, and deletion of CDKN2A/ B, which encodes for p16 and p14.…”
Section: Cell Cycle Regulationmentioning
confidence: 99%
“…Agrawal and colleagues published the first exome-sequencing study of esophageal cancer, sequencing 12 ESCCs and 11 EACs as well as matched non-neoplastic tissues from subjects in the United States [31] , and a handful of NGS studies in ESCC have been published over the last four years (summarized in Table 2) [31][32][33][34][35] . Genetic aberrations identified within these studies, including gene mutation, gene rearrangement, and gene amplification/deletion, increased the understanding of constitutive activation of oncogenes, or loss of function of tumor suppressors.…”
Section: Genetic Alterations Driving Esccmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, it was suggested that ZNF750 function was associated with epithelial differentiation (5)(6)(7)10,11). These data suggested that a low expression of ZNF750 is associated with tumor aggressiveness in ESCC.…”
Section: Discussionmentioning
confidence: 83%